UPAYA PEMANFAATAN LIMBAH MELALUI PELATIHAN DAUR ULANG SAMPAH BOTOL PLASTIK MENJADI ALAT PERANGKAP NYAMUK SEDERHANA DAN EKONOMIS - Angrian Permana; Rani Puspa; Rizki Najiulloh; Rian Aji Pangestu; Suhery Suhery; Neneng Masitoh (Yayasan Education and Social Center, 2023)
Natural sustainability need our attention. Plastic waste is a big problem of environmental pollution for the preservation of nature. Plastic waste is one of the wastes that are very difficult to decompose by the soil. So, one of the efforts to avoid environmental pollution is by recycling the plastic waste. This community service activity aims to empower and motivate young people to care and love the environment. This activity is expected to foster a spirit of youth empowerment. This community service provides training on recycling plastic bottle waste by honing youth creativity, so that plastic waste from garbage can be recycled into simple mosquito traps that are environmentally friendly. The method used in this service activity is observation and documentation. The result of this training is the teenagers have the skills and creativity in processing the economical plastic bottle waste